2010
DOI: 10.29309/tpmj/2010.17.04.2965
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Prostatic Disease

Abstract: Objectives: Analysis of the pattern of prostatic disease in Faisalabad. Design of Study: Case series study. Setting: Department of Pathology, University Medical and Dental College (UM&DC) and Meezan Laboratory (ML). Period: Duration of the study is three years. Methods and Materials: All prostatic specimens presenting to the Pathology department at the UM&DC and ML for histopathology were included. Results: During this period 540 prostatic biopsies were examined. The mean age of the patients was 67 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Both receptors are articulated in the adult prostate, ERα expression appears to be restricted to the stromal compartment and ERβ is present in both the epithelial cells and to a lesser extent in the stromal compartment. 8 In our study the age of presentation for malignant lesions ranged from 55 to 84 years with a mean of 68 years was similar to study done by Aslam HM et al and Hameed S et al 7,9 In benign lesions age ranged from 39 to 85 years with a mean age of 63 years. Most of the patients were in 7th decade of life for both benign and malignant lesion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both receptors are articulated in the adult prostate, ERα expression appears to be restricted to the stromal compartment and ERβ is present in both the epithelial cells and to a lesser extent in the stromal compartment. 8 In our study the age of presentation for malignant lesions ranged from 55 to 84 years with a mean of 68 years was similar to study done by Aslam HM et al and Hameed S et al 7,9 In benign lesions age ranged from 39 to 85 years with a mean age of 63 years. Most of the patients were in 7th decade of life for both benign and malignant lesion.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the patients were in 7th decade of life for both benign and malignant lesion. These findings were supported by study done by Hameed S et al and Mansoor I et al 9,10 Aslam HM et al stated that frequency of hyperplasia increases with age from fifth decade to seventh decade, this reflects that hyperplasia may be a normal aging process. 7 According to the study by Naskar S et al mean age of presentation for prostatic lesions were 68.66 years 11 which was analogous to our study.…”
Section: Discussionsupporting
confidence: 70%
“…19 A different study has reported that well-differentiated carcinoma (Gleason score 2–4) is the most frequently diagnosed carcinoma. 20…”
Section: Discussionmentioning
confidence: 99%
“…It is a non neoplastic excessive growth of prostatic glands which results in forming large nodules mostly involving the peri-urethral region of prostate. 6 These nodules encroach the lateral walls of urethra thus causing lower urinary tract symptoms. Prostatic Cancer has become the second most commonly diagnosed malignancy in men after malignancy of lung.…”
Section: Introductionmentioning
confidence: 99%